2016
DOI: 10.1039/c6ce00198j
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of MOF nanoparticle sizes using various physical characterization methods – is what you measure what you get?

Abstract: While the size of nanoparticles (NPs) seems to be a concept established in the field of NPs and is commonly used to characterize them, its definition is not that trivial as different "sizes" have to be distinguished depending on the physical characterization technique performed to measure them. Metal-organic frameworks (MOFs) are known for their crystallinity, their large variety of compositions due to a huge number of inorganic building blocks that can be combined with almost endless organic linkers, their tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 70 publications
4
102
0
6
Order By: Relevance
“…Scanning electron microscopy (SEM) showed that UiO-66-L1 forms well-defined nanoparticles around 100–200 nm in size (Figure S6) in a manner similar to a recently reported modulated synthesis of a related zirconium fumarate MOF 69, 70. In contrast, UiO-66-L2 has a larger particle size, around 400–600 nm (Figure S7), suggesting that click modulation can be used to control nanoparticle size as well as surface chemistry.…”
Section: Resultssupporting
confidence: 81%
“…Scanning electron microscopy (SEM) showed that UiO-66-L1 forms well-defined nanoparticles around 100–200 nm in size (Figure S6) in a manner similar to a recently reported modulated synthesis of a related zirconium fumarate MOF 69, 70. In contrast, UiO-66-L2 has a larger particle size, around 400–600 nm (Figure S7), suggesting that click modulation can be used to control nanoparticle size as well as surface chemistry.…”
Section: Resultssupporting
confidence: 81%
“…The nanoparticle size distribution is, therefore, an intrinsic measure of the control and quality of the synthesis procedure, while the estimated size value only refers to an averaged quantity derived from this distribution. Different techniques present different sensitivity to particles of varying dimensions, and care has to be taken when comparing results obtained from different characterization methods . Techniques with single‐particle resolution, such as high‐resolution microscopy and nanoparticle tracking analysis, are able to provide a number‐based average of particle size, where each particle is assigned an equal weight.…”
Section: Nanoparticle Parametersmentioning
confidence: 99%
“…This endeavor is limited by our ability to fully investigate the nanoscale realm: Different characterization techniques are based on different physical properties, therefore only providing a partial picture of the nanoparticle characteristics. Making matters more challenging yet, the characterization methods themselves can directly affect the measured quantities …”
Section: Introductionmentioning
confidence: 99%
“…For instance, how to standardize some physicochemical characterizations of MOFs in terms of size distribution, shape, colloidal stability, and surface chemistry, and how to obtain the effective synergistic effect in combined therapy strategies. When it comes to the size of MOFs, the state of the sample should also be considered and multiple characterization methods should be adopted . Moreover, the designs of cheaper and less toxic MOFs, such as Mg(II) and Ca(II) MOFs, are an important issue in research on applicable MOFs.…”
Section: Discussionmentioning
confidence: 99%